Hakikat Nilai Budaya Rambu Solo’ Sebagai Pemersatu Masyarakat Suku Toraja - Muhammad Rizal; Lisye Marselina Bure; Nurfhauzia Muhammad; Sarkia Sarkia; Sri Wahyuni Handayani Idang; Amal Arfan (UNIVERSITAS NEGERI MAKASSAR, 2022)
Rambu Solo' Ritual is a funeral service performed by the Torajan tribe as a form of final respect for a person who is his deceased relative. This study aims to find out the concept of the last ceremony of respect for the Toraja community through the culture of the Rambu Solo’ Ritual and community acceptance of the process, as well as to obtain sacred values believed by the Toraja tribal community. The use of methods in this study is used qualitative methods with types of research that utilize qualitative data then descriptively elaborated. The data collection technique was carried out by literature studies from various sources relevant to this study and then described the output of the findings. Based on the output that has been obtained, it is concluded that the Rambu Solo’ Ceremony has become one of the unifying cultural customs of the Toraja tribe. With the principle of